The Japanese Arts and Self-Cultivation. - Carter, Robert E. (State University of New York Press, 2007)
It is through the practice of the arts, and not through rules or theory that moral and spiritual values are taught in Japan. Author Robert E. Carter examines five arts (or "ways" in Japan): the martial art of aikido, Zen landscape gardening, the Way of Tea, the Way of Flowers, and pottery making. Each art is more than a mere craft, for each takes as its goal not just the teaching of ethics but the formation of the ethical individual. Transformation is the result of diligent practice and each art recognizes the importance of the body. Training the mind as well as the body results in important insights, habits, and attitudes that involve the whole person, both body and mind. This fascinating book features the author's interviews with masters of the arts in Japan and his own experiences with the arts, along with background on the arts and ethics from Japanese philosophy and religion. Ultimately, the Japanese arts emerge as a deep cultural repository of ideal attitudes and behavior, which lead to enlightenment itself.